2007
DOI: 10.1002/biof.5520290402
|View full text |Cite
|
Sign up to set email alerts
|

A combination of soy isoflavone supplementation and exercise improves lipid profiles and protects antioxidant defense‐systems against exercise‐induced oxidative stress in ovariectomized rats

Abstract: Menopause is often accompanied with weight gain, metabolic lipid abnormalities, and oxidative stress. In this study, we investigated the combined effects of exercise and soy isoflavone supplementation on the lipid profiles and antioxidant capacities of ovariectomized rats. Twenty-five female Sprague-Dawley rats were divided into 5 groups: sham-operated, ovariectomized (OVX), OVX with exercise (OVX+EX), OVX with soy isoflavone supplementation (OVX+ISO), and OVX with both soy isoflavones and exercise (OVX+ISO+EX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
(41 reference statements)
3
20
0
Order By: Relevance
“…In the present study, 6 weeks of combined oat bran with brisk walking exercise could reduce serum total cholesterol and LDL-C concentrations. Both Oh et al 19 and the present study showed that combined exercise and nutritional supplementation could give beneficial effect on improving lipid profiles. Nevertheless, comparison between Oh et al 19 and the present study showed that shorter study period as in the present study could only reduce total cholesterol and LDL-C, but not triglycerides as reported by Oh et al 19 Therefore it is recommended for lengthening the study duration in future in order to get better results, it is speculated that participants may need longer time to adapt to the exercise and supplementation physiologically.…”
Section: 7%supporting
confidence: 65%
See 2 more Smart Citations
“…In the present study, 6 weeks of combined oat bran with brisk walking exercise could reduce serum total cholesterol and LDL-C concentrations. Both Oh et al 19 and the present study showed that combined exercise and nutritional supplementation could give beneficial effect on improving lipid profiles. Nevertheless, comparison between Oh et al 19 and the present study showed that shorter study period as in the present study could only reduce total cholesterol and LDL-C, but not triglycerides as reported by Oh et al 19 Therefore it is recommended for lengthening the study duration in future in order to get better results, it is speculated that participants may need longer time to adapt to the exercise and supplementation physiologically.…”
Section: 7%supporting
confidence: 65%
“…[18][19][20] According to animal study by Oh et al, 19 combination of soy supplementation and exercise showed its effectiveness by lowering serum total cholesterol, triglycerides and LDL-C in rats. To date, information are lacking on the additional beneficial of combined effects of brisk walking and oat bran consumption compared to oat bran consumption alone and sedentary without consumption of oat bran on body weight, body composition and blood lipid profiles among hypercholesterolemia women aged 40-50 years old.…”
Section: Sports and Exercise Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol changes in postmenopausal women [54] and in rodents after ovariectomy [55,56] are due to a lack of estrogen. Kamei et al [57] identified changes of gene expression in lipid metabolism including a decrease of SREBP1 in ovariectomized mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously reported that ovariectomized rats that underwent an exercise intervention had significantly elevated DNA damage in their lymphocytes compared to those that did not receive exercise [23]. Therefore, even if exercise interventions could lower blood LDL-cholesterol and the atherogenic index, the exercise may need to be monitored to minimize possible DNA damage in cases of estrogen deficiency [23].…”
Section: Introductionmentioning
confidence: 99%